ANNA'S GRIEF IN ‘WHEN MARNIE WAS THERE’ MOVIE: TONKIN'S THEORY - Buntoro, Ruth Shieren (ELite Journal : International Journal of Education, Language and Literature, 2024)
The movie may be used as an auditory and visual communication tool to deliver messages. Every scene and utterance may have a lot of significance and direction that the audience can perceive. This study aims to investigate the processes and stages involved in grief through Tonkin's theory in the movie When Marnie Was There released by Ghibli. This study specifically focuses on the main character, Anna Sasaki. This study analyzes how Anna deals with her grief in four stages, Numbing, Yearning, Disorganization, and Reorganization. Convincing utterances and scenes from the movie are considered the main source of data and used descriptive qualitative method with the unit of study in the form of performance scenes and utterances related to the stages of grief of the main character. According to the results, this study shows that the main character, Anna Sasaki, has gone through the four stages of grief, in which the yearning and disorganization stages are more dominant throughout the movie. Even though in the end in the last stage she finds a reason to move on and chooses to return to being happy, the grief that has been haunting her has remained with her.